URGENSITAS LITERASI GENERASI MUDA DALAM MENDORONG DAYA SAING DESA KARANGPATIHAN - Setyowulan, Endang Sarwiningsih; Wardhani, Windi Novia Ratri (Fokus ABDIMAS, 2024)
This community engagement aims to enhance literacy and reading interest in Karangpatihan Village, a remote village in the hinterland area. We implemented a community program consisting of a series of activities, including the establishment of a village library, book clubs, literacy workshops for children and adults, and literacy campaigns at the village level. Through collaborative approaches with the village government, local schools, and the community, we successfully created an environment that supports and stimulates reading interest among the residents of Karangpatihan Village. We also engaged local role models, such as teachers, community leaders, and writers, to provide additional motivation to the community in improving literacy. Program evaluation indicates a significant improvement in reading interest and literacy skills among children, teenagers, and adults in Karangpatihan Village. We believe that the steps we have taken not only help enhance the quality of life and knowledge of the community but also have long-term positive impacts in unlocking potential and strengthening the local community.